Predictive and prognostic significance of tumor-infiltrating lymphocytes in patients with breast cancer treated with neoadjuvant systemic therapy - Melichar, Bohuslav; Študentova, Hana; Kalábová, Hana; Vitásková, Denisa; Čermáková, Petra; Hornychová, Helena; Ryška, Aleš (Anticancer research, 2014)
Despite the progress of tailored therapeutic strategies in patients with breast cancer, there is an unmet medical need for additional biomarkers that would guide therapy, including the administration of targeted agents. It has been demonstrated that the presence of tumor-infiltrating lymphocytes (TILs) is associated with prognosis in patients with early breast cancer. Moreover, TIL counts were shown to predict outcome of neoadjuvant chemotherapy. The neoadjuvant setting is increasingly used to assess the efficacy of new systemic therapies, and TILs are promising as a biomarker reflecting the immune response to tumor. Future studies should investigate on the integration of TILs as predictive biomarkers in patients treated with targeted- agents.
Keywords: Prognosis; Neoadjuvant Therapy; Lymphocytes, Tumor-Infiltrating; tumor-infiltrating lymphocytes; ženské pohlaví; nádory prsu; review; lidé; neoadjuvantní terapie; prognóza; Breast cancer; Humans; Female; tumor infiltrující lymfocyty; Breast Neoplasms; targeted therapy